Note on the malaria outbreak in users of injectable drugs - Barata, Luiz Carlos Barradas (1990)
An outbreak of Plasmodium vivax malaria among drug addicts in Bauru, S. Paulo State, Brazil, is reported. Until July 1989,12 cases had been confirmed by thick smear examinations and 20 contacts were being investigated. All of them reported frequent use of intravenous cocaine and sharing of needles and syringes but deny having travelled through endemic malarial areas.